Pendampingan Masyarakat Desa Tulungrejo dan Desa Sumber Brantas dalam Kajian Kerentanan terhadap Risiko Perubahan Iklim - Anggraeni Hadi Pratiwi; Talifatim Machfuroh; Dyah Pitaloka; Zainal Abidin; Arief Lukman Hakim; Arum Sekar Buana (I-Com: Indonesian Community Journal, 2024)
The main problem that occurs in the upstream area of the Brantas watershed is the high level of erosion due to ecologically incorrect horticultural farming models and methods. This condition causes vulnerability for society in facing climate change. The aim of this service activity is to determine the level of vulnerability to risks due to climate change in Tulungrejo and Sumber Brantas. This activity carried out in two villages, Tulungrejo and Sumer Brantas in February 2021. Three main activities were carried out, namely Focus Group Discussion (FGD), climate change risk analysis using Analisa 4 Jendela method, and climate change risk analysis using 5W+1H. Tulungrejo and Sumber Brantas are classified as areas that have a mild to moderate risk level in the agricultural sector. The threat of high rainfall causes flooding to become one of the causes of high risk in various strategic areas because it occurs in places that have high vulnerability. Keywords: Community Assistance, Vulnerability, Climate Change